Spinning Survival with Witch Words: What Mary Daly Taught Me about Theological Language. - Settle, Zachary Thomas (Journal of Feminist Studies in Religion (Indiana University Press))
Though the play of Mary Daly's use of language has been both praised and problematized, theoretical analyses of her linguistic interventions remain largely underdeveloped. This essay aims to make sense of Daly's poetic, playful employment of language by reading it through Judith Butler's notion of performativity. In this essay, Settle argues that Daly's philosophic wordplay is a creative mode of performative linguistics, which is simultaneously mandated and made possible by the repetition of patriarchy's marginalizing acts. At the same time, a careful analysis of Butler's performativity and speech act theory reveals the ways that Daly's linguistic labors have intervened and disrupted the logics and structures of that discourse. Daly's creative manipulation of language, then, continues to perform as an alternative mode of theology beyond patriarchy, and Daly herself—even in her post-theological state—revealed something significant to theology about its own linguistic possibilities.